Hubungan antara Kepribadian, Kesiapan Organisasi untuk Berubah dan Kriteria Universitas Kelas Dunia - Azhar El Hami (Psympathic : Jurnal Ilmiah Psikologi, 2016)
Changes in the organization is important to retain its existence and continues to grow. This study attempted to see the connection between personality factors (the big five factor), organizational change readiness and the criteria of World Class University at University X. Based on the analysis of qualitative and statistical tests associated with the third link variable, then showed that the personality and organizational change readiness have an important role for the achievement of world class criteria university. This research showed that personality profiles of  extraversion and openess to experience as well as aspects of the vision of change and acceptance phase to be decisive for the index of world class university. This result seems to be supported by the presence of the relationship between extraversion profile with aspects of the vision of change and acceptance. The profile of openness to experience also correlated with aspects of vision of change and acceptance.